Drug-Coated Balloon for De Novo Coronary Artery Lesions: A Systematic Review and Trial Sequential Meta-analysis of Randomized Controlled Trials - Wei Liu; Min Zhang; Guangping Chen; Zongzhuang Li; Fang Wei (Cardiovascular Therapeutics)
Objective. To investigate the efficacy of drug-coated balloon (DCB) treatment for de novo coronary artery lesions in randomized controlled trials (RCTs). Background. DCB was an effective therapy for patients with in-stent restenosis. However, the efficacy of DCB in patients with de novo coronary artery lesions is still unknown. Methods. Eligible studies were searched on PubMed, Web of Science, EMBASE, and Cochrane Library Database. Systematic review and meta-analyses of RCTs were performed comparing DCB with non-DCB devices (such as plain old balloon angioplasty (POBA), bare-metal stents (BMS), or drug-eluting stents (DES)) for the treatment of de novo lesions. Trial sequential meta-analysis (TSA) was performed to assess the false positive and false negative errors. Results. A total of 2,137 patients enrolled in 12 RCTs were analyzed. Overall, no significant difference in target lesion revascularization (TLR) was found, but there were numerically lower rates after DCB treatment at 6 to 12 months follow-up (RR: 0.69; 95% CI: 0.47 to 1.01; P=0.06; TSA-adjusted CI: 0.41 to 1.16). TSA showed that at least 1,000 more randomized patients are needed to conclude the effect on TLR. A subgroup analysis from high bleeding risk patients revealed that DCB treatment was associated with lower rate of TLR (RR: 0.10; 95% CI: 0.01 to 0.78; P=0.03). The systematic review illustrated that the rate of bailout stenting was lower and decreased gradually. Conclusions. DCB treatment was associated with a trend toward lower TLR when compared with controls. For patients at bleeding risk, DCB treatment was superior to BMS in TLR.